Cystic Fibrosis assessment in infertile couples: genetic analysis trough the Next Generation Sequencing technique - Elena D'Alcamo; Giuseppe Gullo; Gaspare Cucinella; Antonino Perino; Sofia Burgio; Andrea Etrusco; Veronica Agrigento; Serena Sclafani; Florinda Listi; Aurelio Maggio; Igea Vega; Antonio Simone Laganà; et al. (IMR Press, 2022)
Background: Cystic Fibrosis (CF) is a genetic disease which is responsible for different systemic conditions. In particular, CF could be responsible for infertility, especially in the male partner due to congenital bilateral absence of vas deferens (CBAVD). Moreover, in Assisted Reproductive Techniques CF screening is performed in order to detect possible risks for the newborn. For this reason, CF testing is one of the main genetic screening performed in infertile couples. Methods: In this scenario, we present a prospective observational study in CF testing with Next Generation Sequencing (NGS) technique on 360 subjects referring to an In-Vitro Fertilization center. Results: 360 subjects were screened for CFTR. Of them, 19 subjects presented CF causing variants, 44 subjects presented CFTR-RD associated, 22 subjects had variants of uncertain significance and 19 subjects with no clinical consequences. Conclusion: Results clarify proportions of the main CF mutations. Actually, there are no more advanced techniques rather than Next Generation Sequencing (NGS) technique, although it is not yet widely used as a test for the identification of the CF carrier.